Rapid Detection of D-dimer Using a Fiber Optic Biosensor - Rowe, Chris A.; Bolitho, Jeni S.; Jane, Andrew; Bundesen, Peter G.; Rylatt, Dennis B.; Eisenberg, Paul R.; Ligler, Frances S. (Thrombosis and Haemostasis, 1998)
We describe a rapid and sensitive method for detection and quantification of D-dimer and other crosslinked fibrin degradation products (XL-FDPs), which are present in elevated concentrations in patients with sepsis and thrombotic disorders. The method utilizes a sandwich fluoroimmunoassay immobilized in the sensing region of an evanescent wave biosensor. Physiological concentrations of D-dimer and high molecular weight XL-FDP could be determined in buffer and plasma samples on calibrated fibers in 11 min. Samples from septic patients were assayed using ELISA and the fiber optic method; concentrations determined by fiber optic assay were strongly correlated with those determined by ELISA (r = 0.918); intra- and inter-assay errors were comparable to those from ELISAs. Given its accuracy and rapid response time, this fiber optic biosensor shows great potential for development as a diagnostic tool.